Child Protection in Mixed Marriages Between Indonesia and The Netherlands: a Settlement Through the Hague Convention and National Administrative Regulations - Ridha Kurniawan; Said Rizal; Edi Hartono; Alfurqan Muslim; Abd. Sazeli Aziz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Child protection in mixed marriages between Indonesia and the Netherlands often faces obstacles due to fundamental differences in family law, civil registration, citizenship, and cross-border dispute resolution mechanisms. Administratively valid marriages in the Netherlands do not always receive similar recognition in Indonesia, leaving children's identities and legal status uncertain. The aim of this study is to comprehensively describe how the two countries regulate the status of children in mixed marriages and to assess any inconsistencies that pose risks to identity security and parenting. The method used is a normative-comparative analysis through a reading of the provisions of BW 1, Rijkswet op het Nederlanderschap, Wet Basisregistratie Personen, the 1980 and 1996 Hague Conventions, and Indonesian regulations such as the Marriage Law, the Population Administration Law, the Child Protection Law, and the Citizenship Law. The analysis shows that the Netherlands has a more integrated mechanism for child protection, supported by a national registration system and international instruments, while Indonesia still relies on religious legality and administrative procedures that often hinder identity registration. The analysis also shows that the asymmetry in the recognition of documents and decisions between countries is a major source of uncertainty regarding children's status. Recommendations include the need to ratify the Hague Convention, strengthen administrative cooperation between Indonesia and the Netherlands, simplify document legalization, and reform the Civil Registration and Civil Registration system to ensure more stable and equitable child protection in both countries.